PERANCANGAN E-REKAPITULASI ALAT TULIS KANTOR (ATK) UNIVERSITAS DIPONEGORO BERBASIS WEB MOBILE - FAUZI, ANAS; AMIN, S.T., M.Kom, FATKHUL (Information Technology and Telematics, 2018)
Abstract - Diponegoro University holds an auction to meet the needs of every year, one of them Stationery Office (ATK). The need for ATK by the number of thousands of items requires more time and energy to recapitulate the needs of all Undip. Problems arise when all workmanship is still manual using the printout list of goods, so the operator who must work extra. If there is a change in the number of needs, the update is still manual. Based on the problem, then made an information system E-Recapitulation Stationery Office (ATK) Diponegoro University Mobile Web-Based with the design and manufacturing process begins by making system design and business process flow. System creation using phpMyAdmin coding. Last is device implementation and testing for system feasibility. The result is an information system can help and accelerate the process of recapitulation of ATK data that can be processed immediately. It is expected that the system can be developed to the payment phase in order to facilitate in handling the demand of goods along with payment.Keywords: recapitulation, stationery, bootstrap, information systemDAFTAR PUSTAKA[1] Yuniarta, S. Risdianto, T. Dhebora, M. Fatchiyah. (2017). “Aplikasi Rekapitulasi Inventaris Sekolah Berbasis Web.” Makalah Proyek Akhir ITS, Srabaya.[2] Vikaranda, A. (2015). “Perancangan Sistem Rekapitulasi Online Pada CV Ardian Jaya Mandiri Berbasis Web Menggunakan Framework YII”. Makalah Skripsi Gunadarma, Jakarta.[3] Abdyrahman, M. (2016). “Sistem Informasi Jadwal Perkuliahan Berbasis Web Mobile  Pada Politeknik Sains Dan Teknologi Wiratama Maluku Utara”. Jurnal Politeknik Sains Dan Teknologi Wiratama, Maluku Utara[4] Fitzgerald, J. (2014). “Business Data Communications and Networking”. Journal International 12th Edition[5] Nugroho, B. (2008). Latihan Membuat Aplikasi Web PHJP dan MYSQL dengan Dreamweaver MX (6,7,2004) dan 8. Yogyakarta: Gava Media.[6] Gie. (2007). Administrasi Perkantoran Modern. Yogyakarta:Andi.[7] Windhya Kusuma Wardana, Bagus. (2010). “Aplikasi Inventaris Kantor pada Sekretariat Daerah Provinsi Kalimantan selatan”. STIMIK Banjarbaru.[8] Al Fatta, Hanif. (2009). Analisis dan Perancangan Sistem Informasi untuk Keunggulan Bersaing Perusahaan dan Organisasi Modern. Yogyakarta:Andi.[9] Kusrini. (2007). Strategi Perancangan dan Pengelolaan Basis Data. (A. H. Triyuliana, Ed.). STMIK AMIKOM Yogyakarta: CV. ANDI OFFSET. Retrieved from https://books.google.co.id/books?id=0_FAskY4xZgC&pg=PA28&dq=pengg ambaran+erd&hl=id&sa=X&redir_esc=y#v=onepage&q=penggambaran erd&f=false[10] Raymond, J., & Scell, G. (2008). Sistem Infomasi Management. (N. Setyaningsih, Ed.) (10th ed.). Jakarta: Salemba Empat.[11] Gregorius, A. (2000). PHP dan MySQL dengan editor Dreamweaver MX. ANDI: Yogyakarta”[12] B’Far, R. (2005). “Mobile Computing. Principles. Designing and Developing.” Journal Cambridge University Press, New York[13] Ismail, T. Thohari, F. (2010). “Sistem Penggajian Berbasis Mobile Web Di Dircomnet Yogyakarta”. Jurnal Informatika Vol 4, No. 2, Juli 2010.[14] Fransisco,Y. Novianto. (2016). “Perancangan Sistem Pengolahan Data Angkutan Pada PT. Anugrah Guna Mustika Jambi”. Jurnal Stikom Dinamika Bangsa, Jambi. [15] Rachmat, H. (2014). “Aplikasi Pengadaan Langsung Aktiva Dibiayakan Berbasis Web Local.”  Vol 2, No 2 (2014): Jurnal Evolusi 2014